2004
DOI: 10.1182/blood-2004-03-1155
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic changes from before transplantation to 1 year in patients receiving myeloablative allogeneic hematopoietic cell transplant

Abstract: Research indicates that myeloablative hematopoietic cell transplantation (HCT) impairs neurocognitive function. However, prospective studies on long-term effects are lacking. This longitudinal study examined neurocognitive changes over the first year in 142 adult recipients of allogeneic HC transplants who received neuropsychologic testing before transplantation and again after 80 days and 1 year. Age-, sex-, and education-adjusted population-based standardized scores were used for normative comparisons. Perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 22 publications
(29 reference statements)
7
84
5
1
Order By: Relevance
“…Our results look at recovery during the first year after transplantation, whereas previous work has shown that full recovery may take 3-5 years. 20,34 Further follow-up is needed to determine if pre-transplantation QOL is predictive of QOL several years post transplantation. In addition, precise assessment of disease risk is limited by the heterogeneity of the diagnoses in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our results look at recovery during the first year after transplantation, whereas previous work has shown that full recovery may take 3-5 years. 20,34 Further follow-up is needed to determine if pre-transplantation QOL is predictive of QOL several years post transplantation. In addition, precise assessment of disease risk is limited by the heterogeneity of the diagnoses in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment correlated with neuroradiological peculiarities, in particular diffuse damage in the white matter that in turn is associated with deficits in attention and information-processing speed. 37 Syrjala et al 38 investigated 142 patients at three time points (pre-HSCT, and 80 days and 1 year post-HSCT). They observed significant reductions in neuropsychological performance throughout between the first and second time points.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cognitive changes generally include a large age range and samples of either autologous and alloHCT patients, 18,20,22 or only patients receiving myeloablative alloHCT. 21,23,24 To our knowledge, the impact of non-myeloablative alloHCT on cognitive functioning in older adults is not known.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…29 Arora et al 30 found that patients with low income were over three times as likely to report frailty after transplant. 23 Therefore, financial stress negatively impacts patients' long-term health and ongoing treatment decisions.…”
Section: Functional Considerationsmentioning
confidence: 99%